Engineered Orthogonal Quorum Sensing Systems for Synthetic Gene Regulation in Escherichia coli - Tekel, Stefan J.; Smith, Christina L.; Lopez, Brianna; Mani, Amber; Connot, Christopher; Livingstone, Xylaan; Haynes, Karmella A. (Frontiers in Bioengineering and Biotechnology, 2019)
Gene regulators that are controlled by membrane-permeable compounds called homoserine lactones (HSLs) have become popular tools for building synthetic gene networks that coordinate behaviors across populations of engineered bacteria. Synthetic HSL-signaling systems are derived from natural DNA and protein elements from microbial quorum signaling pathways. Crosstalk, where a single HSL can activate multiple regulators, can lead to faults in networks composed of parallel signaling pathways. Here, we report an investigation of quorum sensing components to identify synthetic pathways that exhibit little to no crosstalk in liquid and solid cultures. In previous work, we characterized the response of a single regulator (LuxR) to ten distinct HSL-synthase enzymes. Our current study determined the responses of five different regulators (LuxR, LasR, TraR, BjaR, and AubR) to the same set of synthases. We identified two sets of orthogonal synthase-regulator pairs (BjaI/BjaR + EsaI/TraR and LasI/LasR + EsaI/TraR) that show little to no crosstalk when they are expressed in Escherichia coli BL21. These results expand the toolbox of characterized components for engineering microbial communities.